Merdeka Belajar Application Training for Teacher of SMP Negeri 1 Hamparan Perak - Abdul Meizar; Heri Gunawan; Nurhayati Nurhayati (PT. Marosk Zada Cemerlang, 2022)
Merdeka Belajar is one of the programs from the Ministry of Education, Culture, Research and Technology which is currently being promoted. Carrying out students who freely find their learning rights based on their interests and intelligence. Merdeka Belajar is a government program based on a web application platform. This application is a forum for students who will seek knowledge that can be reached through the gadgets that are currently available. However, the implementation of the Merdeka Belajar program has problems, namely its use. Not all school community members can use it. Especially among teachers who in fact always carry out face-to-face (conventional) learning activities. Through this application learning can be done via online or offline. Especially for SMP Negeri 2 Hamparan Perak teachers who are still having trouble using the Merdeka Belajar application. So that the training was carried out at the request of the School to the Universitas Potesi Utama to hold training on the Merdeka Belajar Application. With the training carried out, the teacher's improvement in the use of the Merdeka Belajar application can increase.